Effectiveness of Nutrition Education to Reduce the Risk of Sports Injury in Young Soccer Athletes - Afriani, Yuni; Sari, Siska Puspita; Sucipto, Adi; Puspaningtyas, Desty Ervira; Elityasari, Cindy Nur; Setiawan, Andika (Media Gizi Indonesia, 2023)
Physical exercise is the main factor in improving the performance of athletes. Physical exercise may cause fatigue and increase the risk of injury. Most athletes have experienced injuries during training or competing, such as muscle pain, sprains, muscle tension, bruises, and minor injuries. The majority of athletes lack knowledge regarding the management of injuries through appropriate nutritional interventions. The importance of proper nutrition therapy education as one of the solutions to reduce the risk of sports injury. The purpose of this study was to observe the change in knowledge about proper nutritional therapy in dealing with injuries in young soccer athletes at PSS Sleman Development Center. The study was conducted in July 2022. The provision of education was given at the Macanan Field, Prambanan, Yogyakarta. The respondents were 22 U-16 athletes at PSS Sleman Development Center. Athletes were given a knowledge questionnaire before and after the provision of education. Data were analyzed using statistical software with descriptive analysis and Wilcoxon Signed Rank Test. The increase in athletes' knowledge was measured from the knowledge score before giving education, which was 86,36 and after being given education increased to 89,09 with an average difference of 2,73 (p=0,366). The maximum score after providing education is 100 with a minimum score of 60. Providing education to athletes can increase athlete's knowledge and understanding of the importance of proper nutritional intake in reducing the risk of sports injury.